2020
DOI: 10.1111/1365-2435.13634
|View full text |Cite
|
Sign up to set email alerts
|

Flowering phenology of a widespread perennial herb shows contrasting responses to global warming between humid and non‐humid regions

Abstract: Plant phenology was assessed as one of the most key Essential Biodiversity Variables on species functional traits, which underpins a variety of aspects of ecosystem function and is a vital determinant of species distribution. Flowering phenology is one of the most sensitive indicators of the effects of recent climatic change. Understanding of intraspecific variation in phenological responses to climate change can contribute to the accurate prediction of phenology and the assessment of potential impacts of clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 71 publications
6
29
2
Order By: Relevance
“…For example, increased temperatures in late summer and early autumn could promote bud cell growth more quickly because of higher mean temperatures in late summer and early autumn than in early spring (24.9 versus 13.5°C). This would be consistent with results from some studies showing stronger temperature sensitivities of spring phenology at warmer locations (Menzel et al 2006, Chen and Xu 2012, Dai et al 2014, Wang et al 2015, Song et al 2020a). Another possible mechanism could be that bud development in the autumn may be more tightly and differently linked to spring phenology in subtropical species than they are in temperate areas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, increased temperatures in late summer and early autumn could promote bud cell growth more quickly because of higher mean temperatures in late summer and early autumn than in early spring (24.9 versus 13.5°C). This would be consistent with results from some studies showing stronger temperature sensitivities of spring phenology at warmer locations (Menzel et al 2006, Chen and Xu 2012, Dai et al 2014, Wang et al 2015, Song et al 2020a). Another possible mechanism could be that bud development in the autumn may be more tightly and differently linked to spring phenology in subtropical species than they are in temperate areas.…”
Section: Discussionsupporting
confidence: 91%
“…showing stronger temperature sensitivities of spring phenology at warmer locations (Menzel et al 2006, Chen and Xu 2012, Dai et al 2014, Wang et al 2015, Song et al 2020a). Another possible mechanism could be that bud development in the autumn may be more tightly and differently linked to spring phenology in subtropical species than they are in temperate areas.…”
Section: Discussionmentioning
confidence: 97%
“…We found that associations between temperature and phenology differed among groups but that the magnitude of these associations generally reflected the different groups' phenology shifts observed over time. This strongly suggests a link between the phenology shifts and climate change, corroborating previous studies such as the ones by CaraDonna et al 2014and Song et al (2020). We found that plants were generally more sensitive to temperature, i.e., their phenology advanced more strongly, than insect pollinators.…”
Section: Temperature Sensitivities Of Plant and Insectssupporting
confidence: 93%
“…Our study's measure of phenology, peak occurrence time, does not account for temporal variation of spatial representation of records within Germany, although some areas might be over-or underrepresented in some parts of the studied period. Moreover, our study also does not account for spatiotemporal variation in macro-and microclimate which can influence intraspecific variation in phenology shifts (Song et al, 2020) and could therefore potentially induce local mismatches.…”
Section: Caveatsmentioning
confidence: 99%
“…In six out of nine cases where the snow melt treatment shifted phenology, either alone or in conjunction with the warming treatment, the effect of the snow melt treatment persisted after GDD was included in the model (Figure 4), supporting the hypothesis that snow melt affects phenology independent of temperature accumulation. It has been previously suggested that the influx of soil moisture after snow melt helps drive the onset of flowering (Dorji et al, 2013;Song et al, 2020;Walker et al, 1995), and this may be the mechanism behind our observed effect of snow melt on phenology. There is also observational evidence that rainfall and soil moisture affect flowering phenology in other, arid ecosystems (Crimmins et al, 2010;Gordo & Sanz, 2010;Peñuelas et al, 2004;Pérez-Ramos et al, 2020;Song et al, 2020).…”
Section: Discussionmentioning
confidence: 56%